Performance Analysis of UWOC using SISO and SIMO Techniques. Issue 6 (July 2021) - Aravind, Jinka Venkata; Kumar, Sanjay; Prince, Shanthi
Abstract: Underwater communication technology is challenging and so far, there is no alternate to sonar technology for wireless communication. Recently, optical wireless communication is proposed to establish reliable communication link underwater. In this paper, underwater wireless optical communication link is simulated under SISO, SIMO communication model techniques using OptiSystem tool. Link distance is enhanced by increasing the number of receivers in the communication model technique for UWOC system. The performance parameters such as bit error rate, quality factor are analyzed under different UWOC model technique for different link lengths. It is observed that as the number of receivers is increased in the communication model technique, the UWOC efficiency improves in terms of Q factor and BER.